How is Etuaptmumk/Two-Eyed Seeing characterized in Indigenous health research? A scoping review. - Sophie I G Roher; Ziwa Yu; Debbie H Martin; Anita C Benoit (PLoS ONE)
Our scoping review sought to consider how Etuaptmumk or Two-Eyed Seeing is described in Indigenous health research and to compare descriptions of Two-Eyed Seeing between original authors (Elders Albert and Murdena Marshall, and Dr. Cheryl Bartlett) and new authors. Using the JBI scoping review methodology and qualitative thematic coding, we identified seven categories describing the meaning of Two-Eyed Seeing from 80 articles: guide for life, responsibility for the greater good and future generations, co-learning journey, multiple or diverse perspectives, spirit, decolonization and self-determination, and humans being part of ecosystems. We discuss inconsistencies between the original and new authors, important observations across the thematic categories, and our reflections from the review process. We intend to contribute to a wider dialogue about how Two-Eyed Seeing is understood in Indigenous health research and to encourage thoughtful and rich descriptions of the guiding principle.